INVESTIGATING THE NEPHROPROTECTIVE POTENTIAL OF OKRA (ABELMOSCHUS ESCULENTUS) AGAINST CISPLATIN-INDUCED NEPHROTOXICITY IN WISTAR ALBINO RATS - SWARUPA RANI G,; SUJATHA D,; PRASAD KVSRG, (Asian Journal of Pharmaceutical and Clinical Research, 2025)
Objective: Plants incorporated in the daily diet are known for their role in disease prevention owing to their diverse biological and pharmacological activities. The present study aimed to investigate the nephroprotective potential of hydro-alcoholic pod extract of Okra (Abelmoschus esculentus) against cisplatin-induced nephrotoxicity. Methods: The chemical constituents of Okra extract were identified through preliminary phytochemical screening and liquid chromatography-mass spectrometry (LC-MS) spectral analysis. A total of 80 compounds were detected, including phytoconstituents with notable antioxidant properties such as alpha-linolenic acid, quercetin, myricitrin, quercetin-3-glucoside-7-xyloside, dioctyl hexanedioate, and protobassic acid. Nephroprotective activity was evaluated in albino Wistar rats at two dose levels (200 and 400 mg/kg b.w.). Nephrotoxicity was induced by a single intraperitoneal injection of cisplatin (6 mg/kg b.w.). The protective effects were assessed by estimating urinary total protein, creatinine clearance, serum creatinine (SC), blood urea nitrogen, lipid peroxidation, and antioxidant status. Results: Nephrotoxicity arose in the group II rats due to cisplatin injections; according to this, SC and urea levels were significantly higher (p<0.05) when compared with the normal control group (I). Animals that received the hydroalcoholic extract of pods of Okra alone (group-V) exhibited no change in serum and urinary functional parameters. Animals that received the hydroalcoholic extract of pods of Okra alone (group-V) exhibited no change in serum and urinary functional parameters. Hence, the hydroalcoholic extract of pods of Okra did not show any nephrotoxic effects. Administration of hydroalcoholic extract of pods of Okra at 200 mg/kg to cisplatin-injected rats improved of blood urea and SC activity in treatment group III animals, when compared to cisplatin-induced group animals (group-II). It was practically near the normal values related with the normal group animals. On administration of hydroalcoholic extract of pods of Okra in treatment groups III and IV animals, a momentous dose-related reduction in the levels of blood parameters was detected when compared to the negative group-II animals. Conclusion: The findings suggest that Okra hydro-alcoholic extract possesses strong nephroprotective activity, likely attributable to its antioxidant phytoconstituents. Hence, Okra may serve as a promising dietary intervention for mitigating cisplatin-induced nephrotoxicity.